Liquid Crystals in Biotribology Synovial Joint Treatment - Ermakov, Sergey; Beletskii, Alexandr; Eismont, Oleg.; Nikolaev, Vladimir; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book summarizes the theoretical and experimental studies confirming the concept of the liquid-crystalline nature of boundary lubrication in synovial joints. It is shown that cholesteric liquid crystals in the synovial liquid play a significant role in the mechanism of intra-articular friction reduction. The results of structural, rheological and tribological research of the creation of artificial synovial liquids - containing cholesteric liquid crystals in natural synovial liquids - are described. These liquid crystals reproduce the lubrication properties of natural synovia and provide a high chondroprotective efficiency. They were tested in osteoarthritis models and in clinical practice.
Introduction -- Biomechanics of Joint Synovia -- Brief Review of Liquid Crystals -- Modern Concepts of Friction and Lubrication of Solids -- Modern Concepts of Friction, Wear and Lubrication of Joints -- Effect of Liquid Crystals on Biological Mechanisms of Reducing Joint Friction -- Liquid Crystals as Effective Preparations for Treatment of Joint and Similar Pathologies -- Conclusions.
Keywords: Physics; Orthopedics; Amorphous substances; Complex fluids; Biophysics; Biological physics; Biomedical engineering; Tribology; Corrosion and anti-corrosives.; Coatings; Physics; Biophysics and Biological Physics; Tribology, Corrosion and Coatings; Biomedical Engineering; Soft and Granular Matter, Complex Fluids and Microfluidics; Conservative Orthopedics; Electronic books